Optimization of Antibacterial Gel Preparation Formula of Aloe Vera Leaf Flesh Fraction (Aloe Vera L.) Against Staphylococcus Epidermidis Using Simplex Lattice Design Method - Setyaningrum, Dewi Anggraheni; Kuncahyo, Ilham; Rahmawati, Ismi (East Asian Journal of Multidisciplinary Research, 2024)
Acne is experienced by 90% of teenagers due to infection with the bacteria Staphylococcus epidermidis. Bacterial infections are treated with antibiotics, but excessive use causes resistance, so medicinal plants are used that do not have side effects. (Aloe vera L.) have antibacterial activity because contain anthraquinone compounds. The aim of research is update the optimization of aloe vera leaf gel to increase the effectiveness of use. The research method uses Simplex Laticce Design with HPMC, Karbopol and TEA. The optimum formula concentration of 1.3379% HPMC, 2.540% Carbopol and 0.481% TEA produced predicted and experimental values for adhesion power (7.977 and 7.5 seconds), spreadability (7 and 6.87 cm), pH (6.128 and 6 ), viscosity (246.775 and 265.3 dPa.S) and inhibition zone (23.772 and 22.66mm). The results of the Paired Sample Test for verification data show a p value of 0.430 > 0.05, is not significant difference between the predicted and the experimental.